2018
DOI: 10.1136/archdischild-2018-315723
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of real-time delivery room resuscitation documentation

Abstract: ObjectiveTo assess the accuracy of real-time delivery room resuscitation documentation.DesignRetrospective observational study.SettingLevel 3 academic neonatal intensive care unit.ParticipantsFifty infants with video recording of neonatal resuscitation.Main outcome measuresVital sign assessments and interventions performed during resuscitation. The accuracy of written documentation was compared with video gold standard.ResultsTiming of initial heart rate assessment agreed with video in 44/50 (88%) records; the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Finally, we do not have data on duration of intubation attempts, which may significantly impact first-attempt success rates, adverse TIAEs, and oxygen desaturation. Future studies using video recording carts will facilitate such data collection [41, 42].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we do not have data on duration of intubation attempts, which may significantly impact first-attempt success rates, adverse TIAEs, and oxygen desaturation. Future studies using video recording carts will facilitate such data collection [41, 42].…”
Section: Discussionmentioning
confidence: 99%
“…The strengths of the present study include (1) data collection from review of video recordings allowing detailed monitoring of observed parameters, signal quality and hence enhanced reliability of data20 21; (2) the assessment of SpO 2 and heart rate in a low-resource setting where PPV is performed in room air without the SpO 2 monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…VR-based studies have shown that traditional paper documentation was less accurate than video for early vital signs and at the timing of procedures. 57 VR improves adherence to best practice guidelines and has led to changes in international resuscitation guidelines. These effects can be seen in simulation as well as real-life scenarios, both in high-and low-resource settings.…”
Section: Discussionmentioning
confidence: 99%
“…VR is more accurate in documenting vital sign assessments than paper-based documentation even when done in real-time. 57,58 In addition, it offers the opportunity to objectively analyse the impact of interventions on physiological measures such as heart rate, skin colour or breathing effort. 31,37,39,55,58 Thus, VR is an invaluable tool for improving knowledge on neonatal transition and the effect of interventions during DR care.…”
Section: Vr For Research Purposesmentioning
confidence: 99%